Relationship between the early repolarization pattern and a history of suicide attempts among drug‐free psychiatric patients. Issue 3 (4th May 2022) - Kameyama, Hiroshi; Sugimoto, Kenichi; Kodaka, Fumitoshi; Ito, Kyoko; Nukariya, Kazutaka; Kato, Tomohiro; Shigeta, Masahiro
Abstract: Aim: Suicide attempts are an important severe psychiatric symptom and a clear outcome for mental disorders. Although the relationship between the early repolarization pattern in electrocardiogram and psychiatric disorders has recently been reported, these reports have not been able to exclude the influence of psychiatric drugs. This study aimed to investigate the relationship between the early repolarization pattern and a history of suicide attempts among patients not receiving psychiatric medication. Methods: A total of 71 patients with a history of suicide attempts were investigated, 38 of whom were analyzed for this study. We compared the frequency of the early repolarization pattern between a suicide attempt group and a control group. Then, we investigated the association between the early repolarization pattern and the suicide attempt group by logistic regression analysis, including electrocardiographic findings associated with psychiatric disorders. Results: The findings indicated that the frequency of the early repolarization pattern was significantly higher in the suicide attempt group (n = 20; 52.6%) than in the control group (n = 4; 10.5%) ( P < 0.001), and the results of the logistic regression analysis indicated that the early repolarization pattern was associated with suicide attempts. Conclusions: These findings suggest that the early repolarization pattern is associated with a history of suicide attempts.